INTEGRATION OF EDUCATION WITH CULTURE IN COMPREHENSIVE SCHOOLS (Web of Teachers: Inderscience Research, 2024)
This article provides information on ways to teach students to think creatively and how to use them in the development of the cultural-educational environment, heuristic methods of teaching students independent creative thinking and research. Also, various creative activities were recommended to develop creative thinking and creative research among students.